Assessment of Pulmonary Metastasis in Differentiated Thyroid Carcinoma: Value of HRCT Correlation with Functional Imaging - Kalshetty, Ashwini; Basu, Sandip (World Journal of Nuclear Medicine, 2023)
Pulmonary metastases in thyroid carcinoma demonstrates varying imaging characteristics and disease biology and the outcome. The valuable complimentary role of high-resolution CT (HRCT) in conjunction with functional imaging such as radioiodine scan has been discussed and illustrated in this review along with the varied clinical and imaging presentations of lung metastases from differentiated thyroid cancer (DTC). A multi-modality patient-specific diagnostic approach and awareness about the atypical presentations helps in early identification as well as effective management of these patients, and especially in certain situations that could need multi-disciplinary management. While HRCT of the lungs as an added tool provides detailed visualization of the lung parenchyma, in the era of hybrid imaging, the routine adoption of SPECT-CT in patients with pulmonary metastases (in diagnostic or post-treatment settings) could provide equivalent or even incremental information from further management viewpoint.
Keywords: differentiated thyroid carcinoma; pulmonary metastasis; high resolution CT (HRCT); multiple detector computed tomography (MDCT); radioiodine scintigraphy; chest X-ray; SPECT-CT